Cloning, expression and purfication of the recombinant DNA polymerase I from the hyperthermophilic bacteria geobacillus anatolicus - Çağlayan, Melike. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
The DNA polymerase I gene of a recently described Geobacillus species, Geobacillus anatolicus from a terrestrial hydrothermal vent has been cloned and expressed in Escherichia coli. Evolutionarily conserved regions of DNA polymerase I genes from related organisms were used for designing oligonucleotide primers for the amplification of the unknown DNA polymerase I gene from Geobacillus anatolicus by polymerase chain reaction (PCR) and for its DNA sequencing. Geobacillus anatolicus DNA polymerase I gene contains a long open reading frame of 2637 bases that encodes 878 amino acid residues. Similarity analyses suggested that Geobacillus anatolicus DNA polymerase I may not contain a putative 3'-5' exonuclease activity. However, the conserved regions related to 5'-3' exonuclease activity were observed in the amino acid sequence of Geobacillus anatolicus DNA polymerase I. The entire DNA polymerase I gene excluding the start codon was cloned into pCR-T7/NT-TOPO expression vector and was expressed in Eschericha coli JM109(DE3) strain. The recombinant Geobacillus anatolicus DNA polymerase I fusion protein including an His6-tag at its N terminal part was obtained. The recombinant protein was purified using Ni-affinity and gel filtration chromatography.
Keywords: Thermophilic bacteria.; Microbiological chemistry.